Social Health Insurance: A Key to achieve Universal Health Coverage in Nepal - Poudel, Sujan; Parajuli, Anusha; Paudel, Shishir (Journal of Karnali Academy of Health Sciences, 2023)
Social health insurance, which offers financial security and risk sharing for health care expenses, could be the key to achieving Universal Health Coverage (UHC) in Nepal. The social health insurance program in Nepal has advanced significantly, but many adjustments in the insurance mechanism are needed to make it truly a key to UHC.